The allosteric behavior of Fur mediates oxidative stress signal transduction in Helicobacter pylori - Pelliciari, Simone; Vannini, Andrea; Roncarati, Davide; Danielli, Alberto (Frontiers in Microbiology, 2015)
The microaerophilic gastric pathogen Helicobacter pylori is exposed to oxidative stress originating from the aerobic environment, the oxidative burst of phagocytes and the formation of reactive oxygen species, catalyzed by iron excess. Accordingly, the expression of genes involved in oxidative stress defense have been repeatedly linked to the ferric uptake regulator Fur. Moreover, mutations in the Fur protein affect the resistance to metronidazole, likely due to loss-of-function in the regulation of genes involved in redox control. Although many advances in the molecular understanding of HpFur function were made, little is known about the mechanisms that enable Fur to mediate the responses to oxidative stress. Here we show that iron-inducible, apo-Fur repressed genes, such as pfr and hydA, are induced shortly after oxidative stress, while their oxidative induction is lost in a fur knockout strain. On the contrary, holo-Fur repressed genes, such as frpB1 and fecA1, vary modestly in response to oxidative stress. This indicates that the oxidative stress signal specifically targets apo-Fur repressed genes, rather than impairing indiscriminately the regulatory function of Fur. Footprinting analyses showed that the oxidative signal strongly impairs the binding affinity of Fur towards apo-operators, while the binding towards holo-operators is less affected. Further evidence is presented that a reduced state of Fur is needed to maintain apo-repression, while oxidative conditions shift the preferred binding architecture of Fur towards the holo-operator binding conformation, even in the absence of iron. Together the results demonstrate that the allosteric regulation of Fur enables transduction of oxidative stress signals in H. pylori, supporting the concept that apo-Fur repressed genes can be considered oxidation inducible Fur regulatory targets. These findings may have important implications in the study of H. pylori treatment and resistance to antibiotics.